Analyzing the Linkage Between Renewable and Non-Renewable Energy Consumption and Economic Growth by Considering Structural Break in Time-Series Data - Dogan, Eyup (Pergamon-Elsevier Science Ltd, 2016)
Even though a number of studies investigate the energy-growth nexus, only a small number of the existing studies use estimation techniques with structural break. Furthermore, majority of the existing studies use aggregate energy consumption and thus fail to identify the effects of energy consumption by sources on economic growth. By taking into account the importance of structural break, this study analyzes the short run and the long run estimates as well as the causality relationship between economic growth, renewable and non-renewable energy consumption for Turkey in a multivariate model wherein capital and labor are included as additional variables. By including additional variables into the model, we also attempt to handle omitted-variable bias problem. This study finds that renewable energy consumption has an insignificant impact on economic growth while non-renewable energy consumption has a significant positive effect on it. The coefficients on capital and labor are statistically significant. Furthermore, we have enough evidence to support conservation hypothesis and feedback hypothesis between renewable energy consumption and economic growth in the short run and the long run, respectively, and feedback hypothesis between non-renewable energy consumption and economic growth both in the short run and the long run. Several policy implications are further discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Dogan, Eyup/0000-0003-0476-5177
Keywords: Renewable Energy Consumption; Non-Renewable Energy Consumption; Economic Growth; Structural Break; Granger Causality